Decitabine-Intensified Modified Busulfan/Cyclophosphamide Conditioning Regimen Improves Survival in Acute Myeloid Leukemia Patients Undergoing Related Donor Hematopoietic Stem Cell Transplantation: A Propensity Score Matched Analysis - Li, Ziying; Shi, Wei; Lu, Xuan; Lu, Hui; Cao, Xiena; Tang, Liang; Yan, Han; Zhong, Zhaodong; You, Yong; Xia, Linghui; Hu, Yu; Wang, Huafang (Frontiers in Oncology, 2022)
To identify the benefit of decitabine (Dec) intensified myeloblative conditioning on the outcomes of patients with acute myeloid leukemia (AML) after related donor hematopoietic stem cell transplantation (HSCT), we performed a retrospective matched‐pair study from a pool of 156 patients to evaluate Dec (20 mg/m2/d i.v. on days −11 to −7) intensified modified busulfan/cyclophosphamide (mBuCy) conditioning regimen versus mBuCy regimen in 92 AML patients, with 46 patients in each cohort. The cumulative incidence of grade II -IV acute graft-versus-host disease (aGVHD) was lower in the Dec group (15.2%±0.3% vs. 32.6%±0.5%, P=0.033). Compared with mBuCy group (15.5%±0.3%), a significant higher proportion of limited cGVHD in Dec group (35%±0.6%) was observed (P =0.025). Dec-intensified mBuCy conditioning was associated with better 2-year overall survival (OS) and GVHD-free relapse-free survival (GRFS) (81%±6.2% vs. 59.4%±7.5%, P = 0.03; 58.7%±8.1% vs. 40.9%±7.3%, P = 0.042; respectively). Our results also elucidated that the Dec group had better 2-year OS and lower 2-year cumulative incidence of relapse (CIR) in patients acquiring haploidentical HSCT than that of the mBuCy group (84.8%±7.1% vs. 58.2%±10.3%, P = 0.047; 17.9%±0.8% vs. 40.0%±1.0%, P = 0.036; respectively), which didn’t increase the treatment related mortality and regimens associated toxicities. Dec intensified myeloblative regimen and high-risk stratification were the vibrable associated with OS, leukemia-free survival (LFS) and GRFS in multivariate analysis. In high-risk patients, no differences were found in CIR, OS, LFS and GRFS between the two groups. These data indicated that Dec-intensified mBuCy conditioning regimen was associated with better survival than mBuCy regimen in AML patients, especially in patients undergoing haploidentical HSCT.